Relationship between Strategic Innovation and Competitive Advantage in Kenya - Mongerwa, Newton (Journal of Strategic Management, 2024)
Purpose: The aim of the study was to assess the relationship between strategic innovation and competitive advantage in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Strategic innovation plays a crucial role in achieving and sustaining competitive advantage for organizations. Through strategic innovation, companies can differentiate themselves from competitors by offering unique products, services, or processes that meet the evolving needs and preferences of customers. By continuously innovating and adapting to changes in the market environment, organizations can stay ahead of the competition and maintain their relevance in the industry. Strategic innovation allows companies to anticipate market trends, identify new opportunities, and develop innovative solutions that provide value to customers while also enhancing operational efficiency and profitability. Moreover, strategic innovation enables companies to build strong relationships with customers, suppliers, and other stakeholders, creating a competitive advantage that is difficult for competitors to replicate. Overall, organizations that prioritize strategic innovation are better positioned to achieve long-term success and outperform their competitors in the marketplace. Implications to Theory, Practice and Policy: Resource-based view, dynamic capabilities theory and open innovation theory may be use to anchor future studies on assessing relationship between strategic innovation and competitive advantage in Kenya. Organizations should prioritize creating a culture that fosters innovation at all levels. Governments should implement policies and initiatives to support the development of vibrant innovation ecosystems, including funding for research institutions, incentives for technology transfer, and support for entrepreneurship and startup ecosystems.